PENGARUH RETURN ON ASSETS (ROA) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM (Studi Kasus Pada Bank BUMN yang Terdaftar di Indonesia Stock Exchange Periode 2013-2022) - Maharani, Putri; Prestarika Lukito, Cristine (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of Return On Assets (ROA) and Earning Per Share (EPS) on stock prices in state-owned banks listed on the Indonesia Stock Exchange (Idx) for the period 2013-2022. The method used is descriptive quantitative. The sample used is the bank's financial statements such as: balance sheets, income statements and stock prices at BUMN banks listed on the Indonesia Stock Exchange (IDX) for the period 2013-2022. Based on the partial research results that Return On Asset (ROA) has no significant effect on stock prices with a tcount value < t table (-1.162368 < 1.68595), and a probability of 0.2532> 0.05 H01 is accepted and Ha1 is rejected. Partially Earning Per Share (EPS) has a significant effect on stock prices with a tcount value of 4.40237> table 1.68595, and a probability value of 0.00001 <0.05, then Ha2 is accepted and H02 is rejected. While simultaneously Return On Asset (ROA) and Earning Per Share (EPS) have a significant effect on stock prices with a fhitung value of 21.72472> ftabel 3.25192 with a significant value of 0.00000 <0.05, then Ha3 is accepted and H03 is rejected. The coefficient of determination shows that ROA and EPS with stock prices are 76.16%, the remaining 23.84% is influenced by other factors outside the regression model.